Back Cover: Plasma Process. Polym. 6∕2017. Issue 6 (16th June 2017) - Kim, Hyun‐Ha; Teramoto, Yoshiyuki; Ogata, Atsushi; Takagi, Hideyuki; Nanba, Tetsuya
Abstract : Back Cover: Ammonia is an important feedstock chemical in many commercial chemical products including fertilizer. Recently, ammonia is gathering attention as one of potential hydrogen carriers for long‐distance transport. As a possible alternative of the Haber‐Bosch process, plasma‐catalysis using Ru‐Mg/alumina catalysts is studied and found to be effective in NH3 production at moderate conditions (at 300 °C and ambient pressure). Further details can be found in the article by H.H. Kim et al. on1600157 .